ASSOCIATION OF RESPONSE TO COMBINED INTERFERON ALPHA- 2b AND RIBAVIRIN THERAPY IN PATIENTS OF CHRONIC HEPATITIS C WITH SERUM ALANINE AMINOTRANSFERASE LEVELS AND SEVERITY OF THE DISEASE ON LIVER BIOPSY - Nadeem, Amina; Hussain, Muhammad Mazhar; Aslam, Muhammad; Hussain, Tassawar; Butt, Idrees Farooq; Khan, Saadat Ali; Asad, Ambreen (Journal of Ayub Medical College Abbottabad, 2009)
Background: Raised serum alanine aminotransferase (serum ALT) levels indicate active liver disease while liver biopsy has been considered the ’˜gold standard’ for assessing the severity of disease in patients of chronic Hepatitis C. The response of these patients to standard treatment regimen of interferon (INF)-alpha- 2b and ribavirin for 24 weeks have been studied. Objective: The objective of this study was to evaluate the association of response to combined INF alpha-2b and ribavirin therapy in patients of chronic hepatitis C with serum ALT levels and severity of the disease on liver biopsy. Methods: This quasi experimental study was conducted in Department of Physiology at Army Medical College and Military Hospital, Rawalpindi from January 2006 to February 2007. One hundred and seven diagnosed non cirrhotic chronic hepatitis C patients were studied. Prior to the commencement of treatment, qualitative assay of Hepatitis C Virus (HCV) Ribonucleic Acid (RNA) was done by Polymerase chain reaction (PCR). Knodell Histopathological Index (HPI) was determined on liver biopsy. The standard treatment of INF-alpha-2b, 3 million units 3 times a week subcutaneous, and Ribavirin 800-1200 mg per day was given for 24 weeks. Serum ALT levels were determined before the start of treatment and later at weeks 12 and 24. Qualitative assay of HCV RNA was done by PCR at the end of treatment to determine the response to treatment. Statistical analysis was done on SPSS 15. Results: Out of 107 patients of chronic hepatitis C, 92 (69 males, 23 females) patients (84%) responded to INF-alpha-2b and ribavirin therapy and revealed negative qualitative assay of HCV RNA by PCR at the end of 24 weeks of treatment while serum ALT levels were normal in 88% of patients at 12 weeks and in 97% at the end of 24 weeks of treatment. Knodell HPI revealed mild, moderate and severe disease in 47.7%, 39.9% and 13.1% of patients respectively. No association was established between response to treatment and severity of the disease on liver biopsy (p<0.11) and serum ALT levels (p=0.09). Conclusion: Response to Interferon alpha-2b and ribavirin therapy in patients of chronic hepatitis C is not associated with the levels of serum ALT and the severity of the illness graded on liver biopsy. Keywords: Chronic hepatitis C, interferon, liver biopsy, serum alanine aminotransferase